Optimal Screw Length in Variable-Angle Locking Plate for Distal Radius Fracture - Nakprasert, Chavalit; Sangarnetra , Borvorntam; Tamnao, Aekkasan; Khemaprapa , Panin (Royal Thai Air Force Medical Gazette, 2023)
Background : The distal radius fracture is a common fracture in adult patients. Operative treatment with variable-angle volar locking plate is become increasingly popular and has shown good results. After variable-angle volar locking plate fixation, the most important complication is extensor pollicis longus rupture. Screw penetration of the dorsal cortex is most common cause and may result in tendon irritation and rupture. Therefore, we are interested in optimal screw length for distal radius fracture fixation. The aim of study is postoperative complications prevention. Methods : 10 pairs of fresh-frozen human cadaver wrist were used for this study. The variable-angle locking plates (APTUS Radius 2.5, Medartis, Switzerland) were positioned to the best anatomical fit and proximal from watershed line 3 mm. We labeled variable-angle locking plate holes with number of screw positions. There were number 1-3 in distal row and number 4-5 in proximal row, arranged from lateral to medial. All screw holes were drilled through dorsal cortex with k-wires. Distal row was drilled 90 degrees perpendicular to variable-angle locking plate and proximal row was drilled 15 degrees distally vertical to variable-angle locking plate. A vernier caliper was used to measure screw length between screw head and dorsal cortex for each hole. Result : 20 specimens were tested successfully, The mean of optimal screw length of No.1 screw was 20.89 ± 1.48 mm, No.2 screw was 22.48 ± 1.38 mm, No.3 screw was 21.51 ± 1.35 mm, No.4 screw was 23.74 ± 1.03 mm and No.5 screw was 24.14 ± 1.03 mm. The most of mean of screw length in distal row was No. 2 screw and in proximal row was No.5 screw. Gender factor and wrist side factor were no statistically significant difference in screw length in all screw holes of variable-angle volar locking plate. Conclusion : Using variable-angle volar locking plate in distal radius fracture fixation, The most screw length in distal row was No. 2 screw and proximal row was No. 5 because the direction of screws were near the convex dome of Lister tubercle at dorsal cortex of distal radius. We recommended the placement of optimal screw length wasn’t longer than 24-mm length size both distal row and proximal row. This knowledge could be applied in all patients because gender factor and wrist side factor weren’t correlated with screw length.